2021
DOI: 10.1039/d1dt01629f
|View full text |Cite
|
Sign up to set email alerts
|

Imino(silyl)disilenes: application in versatile bond activation, reversible oxidation and thermal isomerization

Abstract: Two novel disilenes of type ABSi=SiAB bearing N-heterocyclic imino (A = NItBu) and trialkylsilyl (B = SitBu31, B = SitBu2Me 2) groups are reported. The reduced steric demand in 2 results in a highly stable,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 70 publications
0
16
0
Order By: Relevance
“…From this perspective, acyclic silylenes allow for enhanced reactivity, in comparison to cyclic silylenes, since they generally possess a smaller HOMO–LOMO gap with a low-lying excited state and are structurally more flexibile. , Specifically, we have widely utilized N -heterocyclic imine (NHI) ligands in stabilization and reactivity explorations of low-valent main group element complexes . Especially in silicon chemistry, NHI provided remarkable compounds and reactivities such as silepins mentioned above, silanones, , and disilenes . Our studies have shown that the relative favorability of the intramolecular aromatic C–C insertion can be influenced by slight alternations of the iminosilylene substituents.…”
Section: Introductionmentioning
confidence: 99%
“…From this perspective, acyclic silylenes allow for enhanced reactivity, in comparison to cyclic silylenes, since they generally possess a smaller HOMO–LOMO gap with a low-lying excited state and are structurally more flexibile. , Specifically, we have widely utilized N -heterocyclic imine (NHI) ligands in stabilization and reactivity explorations of low-valent main group element complexes . Especially in silicon chemistry, NHI provided remarkable compounds and reactivities such as silepins mentioned above, silanones, , and disilenes . Our studies have shown that the relative favorability of the intramolecular aromatic C–C insertion can be influenced by slight alternations of the iminosilylene substituents.…”
Section: Introductionmentioning
confidence: 99%
“…Recently new unsymmetrically substituted disilenes with polar and twisted SiSi bonds attracted research activities. 4…”
Section: Introductionmentioning
confidence: 99%
“…However, although the key role of ring strain in HEDM was mentioned, it was not quantified for that ring. Transiently stable zwitterionic Si 2 N intermediates and stable Si 2 O products were also very recently reported [20] …”
Section: Introductionmentioning
confidence: 74%
“…Transiently stable zwitterionic Si 2 N intermediates and stable Si 2 O products were also very recently reported. [20] In case of tripnictogeniranes, only the RSE for the all cis trimethyl-substituted derivative of azadiphosphiridine kPpentacarbonyltungsten(0) complex (20.98 kcal/mol) was recently reported. [21] Herein, reference RSE data for parent PnX 2 rings 1-4 El (PnEl 2 for short, if only the heavy atoms forming the rings are used for naming) (Figure 2) are reported, as well as an analysis of the factors affecting them.…”
Section: Introductionmentioning
confidence: 99%